2013
DOI: 10.1088/1612-2011/10/5/055407
|View full text |Cite
|
Sign up to set email alerts
|

High contrast ballistic imaging using a femtosecond optical Kerr gate of SrTiO3 crystal

Abstract: We investigated a ballistic imaging technique using a femtosecond optical Kerr gate (OKG) made of SrTiO 3 crystal (STO). High-contrast images of a 1.41 line pairs per mm (lp mm −1 ) section of the resolution test chart placed behind a turbid medium were obtained. The STO OKG had greater capacity to acquire high quality images at a high optical density than the quartz OKG, showing that the STO is a promising OKG medium due to its large nonlinear susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This single-beam system consists of a highly nonlinear material, sandwiched between two crossed quarter-wave plates, and which has a high Kerr coefficient, a high damage threshold, a fast response time, weak fluorescence noise, and a wide transmission wavelength range. Considering these characteristics, SrTiO 3 is a kind of solid medium that is appropriate for the ultrafast NER effect [4,5]. This makes it useful as a pulse cleaner for ultrashort laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…This single-beam system consists of a highly nonlinear material, sandwiched between two crossed quarter-wave plates, and which has a high Kerr coefficient, a high damage threshold, a fast response time, weak fluorescence noise, and a wide transmission wavelength range. Considering these characteristics, SrTiO 3 is a kind of solid medium that is appropriate for the ultrafast NER effect [4,5]. This makes it useful as a pulse cleaner for ultrashort laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various materials, such as inorganic glasses [5], organic or polymeric materials [6,7], and semiconductors [8] have been prepared via different methods. Among these various promising optical materials, oxide glasses containing heavy atomic (ionic) oxides, such as bismuthate, tellurite, or plumbum oxides, have stimulated great interest because they have the advantages of high chemical and thermal stability, simple fabrication process, low optical loss over large spectral ranges, and high optical damage threshold [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the optical Kerr-gated (OKG) ballistic imaging employed a short time gate to visualize the object hidden in turbid media by selecting the ballistic and snake photons, and suppressing scattering photons, which were applied in investigating the characterization of turbid media such as biological tissue [16], fuel sprays [17], and liquid jets [18]. Recently, we demonstrated time-gated ballistic imaging using SrTiO 3 crystals and time-resolved shape measurements using bismuth-boron oxide glasses [4,8,19], in which we found that comparing with SrTiO 3 crystals the bismuthbased glasses with heavy atomic (ionic) oxides have the larger hyperpolarizability and ultrafast response time, so they can be expected to be promising nonlinear optical materials for time-gated ballistic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…This method [BWU13], [DAN03], [DUC09a], [DUC09b], [ENF07], [HIL01], [YAT05] which belongs to the direct approach, uses an ultrafast pulse source (order of fs or ps) and is the method studied in the current thesis. In reality, when a photon pulse is launched into a slab of tissue, the light exiting the sample can be broken into three components due to the scattering nature of the medium.…”
Section: Time Resolved Optical Imagingmentioning
confidence: 99%
“…Experimentally, an accurate time resolution can be done by utilizing many different physical procedures. Nowadays, the Streak Camera and the Kerr Gate techniques [BWU13], [FED16], [PUR14], [ZHA13] are the two most commonly used. The Streak Camera is a device which operates by transforming the temporal profile of a light pulse into a spatial profile on a detector by causing a time-varying deflection of the light across the width of the detector (dispersion).…”
Section: Time Resolved Optical Imagingmentioning
confidence: 99%